The implementation of block-system learning on the expertise competence of automotive lightweight vehicle engineering in vocational high school - Nurul Burhan; Zainal Arifin (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
The research concerned here was to discover (1) the effectiveness of block-system learning as viewed from the teacher aspect; (2) the effectiveness of such learning as viewed from the student aspect; (3) the effectiveness of such learning as viewed from the facility and resource aspect; and (4) the students' learning achievement after an application of such learning. The study is descriptive and quantitative research, using a survey approach. The data were compiled through observation, questionnaire use, and documentation. The results indicate that (1) the effectiveness of block-system learning as viewed from the teacher aspect is very high in scale; (2) the effectiveness of block-system learning as viewed from the student aspect is very high in scale; (3) the effectiveness of block-system learning as viewed from the facility and resource aspect is high in scale; and (4) with block-system learning, students' learning achievement, as evaluated through UKK (Uji Kompetensi Keahlian or